A 1.3-Mb 7q11.23 Atypical Deletion Identified in a Cohort of Patients with Williams-Beuren Syndrome - Delgado, L.M. (S. Karger AG, 2013)
Williams-Beuren syndrome is a rare multisystem neurodevelopmental disorder caused by a 1.55-1.84-Mb hemizygous deletion on chromosome 7q11.23. The classical phenotype consists of characteristic facial features, supravalvular aortic stenosis, intellectual disability, overfriendliness, and visuospatial impairment. So far, 26-28 genes have been shown to contribute to the multisystem phenotype associated with Williams-Beuren syndrome. Among them, haploinsufficiency of the ELN gene has been shown to cause the cardiovascular anomalies. Identification of patients with atypical deletions has provided valuable information for genotype-phenotype correlation, in which other genes such as LIMK1,CLIP2, GTF2IRD1, or GTF2I have been correlated with specific cognitive profiles or craniofacial features. Here, we report the clinical and molecular characteristics of a patient with an atypical deletion that does not include the GTF2I gene and only partially includes the GTF2IRD1 gene.